CHOICE OF THE ORGANIZATION REFORM DIRECTION TO MANAGE PROJECT SYSTEM DEVELOPMENT - Олег Євгенович Федорович; Світлана Юріївна Даншина (Авіаційно-космічна техніка та технологія, 2020)
The subject of research in the publication is the process of managing the development of a high-tech organization. The object of research is project system development management. The work aims to choose the current direction of reforming a high-tech organization in conditions of limited opportunities. The article solves the following tasks: analyzes the problems of managing the development of the organization, identifies the main areas of reform associated with ensuring the competitiveness of the organization in the market of high-tech products. To substantiate the choice of the current direction of reform external experts are involved to assess several possible areas of development, considering the state and level of maturity of the organization, readiness for reforms, existing business process model, financial opportunities for development processes. Then based on expert assessments and the method of full factorial experiment, the analysis, and comparison of reform options is carried out to select the most relevant direction in the task of project development management. The limited resources of the enterprise and the requirements for the timeliness of reforms lead to the task of optimizing resources for the implementation of the reform project. The multiplicity of options for allocating resources at different stages of the reform project leads to the use of targeted search in the task of resource optimization. The optimization problem is set based on integer (Boolean) programming in two views: local and multi-criteria optimization. Costs, project deadlines, and the risk of successful project implementation were used as criteria for assessing the allocated resources and the success of the reform project. For multicriteria optimization, the significance of individual criteria is assessed. As a comprehensive criterion, a simple additive convolution of local criteria was used. To assess the correctness of the chosen reform option, the method of agent modeling is added. A set of agents has been formed, with the help of which all stages of the development project are simulated. This takes into account the time factor, allocated funds (costs of the organization), the risks of individual stages. The results of agent modeling will allow concluding the expediency and relevance of the choice of development direction for the subsequent project management of the reform. The scientific novelty of the publications to create a method by which derivative data are formed for the enterprise reform project. The publication uses the following methods: system analysis to justify and choose the direction of development; expert assessments for the formation of a factor experiment plan; the method of full factorial experiment, which allows to evaluate several options for reform and choose the current direction of development of the organization; method of integer (Boolean) programming for the purposeful choice of means during project implementation for development; the method of agent simulation modeling to simulate the implementation of individual stages of the development project. Conclusions: the proposed approach allows at the stage of a preliminary study of the development of the organization to choose the current direction of reform, considering the state of the high-tech organization, readiness to reform, as well as limited opportunities in the face of challenges and threats in the economy.